2002
DOI: 10.1080/000164802320396303
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Expression of Adenovirus-mediated lacZ Gene in Murine Nasal Mucosa

Abstract: Adenovirus is a good tool for transferring exogenous genes into various organs because the virus has a wide spectrum of infection. In this report, we demonstrate that a recombinant adenovirus, Ax1CAlacZ, can transfer an exogenous lacZ gene into murine nasal mucosa in vivo. The efficiency of the exogenous gene expression varied for different cell types and was improved by optimizing the method of administration. In the olfactory region, the olfactory epithelia, sustentacular cells and olfactory nerve efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…In fact, in a previous study, we have reported that expression of CFTR specifically in ciliated cells of CF mice did not alter nasal PD values (26). Because some vectors more readily transduced OE compared with CE (2,17,32) it is critical to know from which cell type a "correction" is being measured. While the CF NP gives a less robust signal with regard to both Na ϩ absorption and Cl Ϫ transport defects, the nasopharyngeal PD assay may be better for ascertaining gene transfer to the ciliated epithelium of the CF mouse.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, in a previous study, we have reported that expression of CFTR specifically in ciliated cells of CF mice did not alter nasal PD values (26). Because some vectors more readily transduced OE compared with CE (2,17,32) it is critical to know from which cell type a "correction" is being measured. While the CF NP gives a less robust signal with regard to both Na ϩ absorption and Cl Ϫ transport defects, the nasopharyngeal PD assay may be better for ascertaining gene transfer to the ciliated epithelium of the CF mouse.…”
Section: Discussionmentioning
confidence: 95%
“…Ramadan and coworkers 10 have successfully used reovirus to create the first mouse model for viral sinusitis. Early gene transfer experiments using adenoviral vectors have been performed by Arimoto and colleagues 11 . This group used an adenovirus vector to transfer exogenous lacZ genes into nasal mucosa of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Early gene transfer experiments using adenoviral vectors have been performed by Arimoto and colleagues. 11 This group used an adenovirus vector to transfer exogenous lacZ genes into nasal mucosa of mice. Our group and others have evaluated at the effects of nasal foreign bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have reported correction of the abnormal nasal PD in CF mice using gene transfer protocols, these studies did not attempt to target a specific cell type. [31][32][33][34] In fact, it has been reported that the olfactory epithelia is more susceptible to gene transfer by adenovirus than the respiratory epithelia, 44,45 and in one study, it was clearly demonstrated that both respiratory and olfactory epithelia were transduced. 31 To restore normal nasal bioelectrics to the CF mouse, correction of both the olfactory and the respiratory epithelia may be required.…”
Section: Cftr Expression In Murine Ciliated Cells Le Ostrowski Et Almentioning
confidence: 99%